Social capital in a capitalocene risk society: An integrative analysis to eco-society structure - Jan Mealino Ekklesia (Journal of Sustainability, Society, and Eco-Welfare, 2026)
Background: Indonesian society facing both escalating natural and anthropogenic disasters. However, the populace is inadequately prepared for this upheaval due to systemic limitations in cultural, strategic, and infrastructural capacity, which classify them as a vulnerable and high-risk society. Theoretically speaking, the Capitalocene paradigm points out that unveiling the capitalist structures behind modernity is essential to truly understand Indonesia’s status as a Risk Society. This study, therefore, aims to explore the potential shift beyond conventional disaster resilience by enhancing societal adaptability to actively confront the risks of the Capitalocene era. Method: This paper utilize the Integrative Literature Review (ILR) method and applies the concepts of the Capitalocene and Chthulucene alongside the social capital model. Finding: The analysis find that social capital, particularly its bonding form, is a crucial factor in enhancing community resilience. It demonstrates a strong relationship with sustainable livelihoods and adaptive capacity across disasters context. Critically, the jeopardized relationship between society and the state is fully exposed through the Capitalocene lens, necessitating the Eco-Society structure to implement three conceptual criteria that address core failures in accountability, knowledge, and relational philosophy. Conclusion: The Eco-Society structure is feasible for implementation within Indonesian society as a necessary framework to confront the Capitalocene Risk Society. Novelty/Originality of this article: As the Eco-Society remains widely unknown in sustainability research, the novelty of this study lies in proposing criteria for its implementation, offering a model applicable to broader research aims and scopes, particularly within the Indonesia context.